Integrasi Nilai Qur’ani dan Hadits dalam Kepemimpinan Kepala Madrasah di Madrasah Ibtidaiyah Bustanul Ulum Banyuanyar Probolinggo - Fina Magfirah Zaini; Ainur Rofiq Sofa (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This study aims to examine the integration of Qur’anic and Hadith values in the leadership of the headmaster at Madrasah Ibtidaiyah Bustanul Ulum Banyuanyar Probolinggo. In the context of Islamic education, leadership based on Qur’anic and Hadith values is crucial for shaping character and improving the quality of education. The research method used in this study is a qualitative approach with techniques such as interviews, observations, and documentation to collect data. The findings show that the headmaster applies Qur’anic and Hadith values in various aspects of leadership, such as decision-making, teacher and student development, and management of madrasah activities. Values such as justice, trustworthiness, wisdom, and compassion, which are found in the Qur'an and Hadith, serve as the main guidelines in carrying out leadership at the madrasah. Moreover, the implementation of these values also positively impacts the motivation and academic achievements of students, as well as strengthens ukhuwah islamiyah (Islamic brotherhood) among the madrasah community. This study concludes that the integration of Qur’anic and Hadith values in the leadership of the headmaster significantly improves the quality of education at Madrasah Ibtidaiyah Bustanul Ulum Banyuanyar Probolinggo.